An Experimental Study of the Unbalance Compensation by Voltage Source Inverter Based STATCOM - Anas Benslimane; Jamal Bouchnaif; Mohamed Azizi; Khalid Grari (Institute of Advanced Engineering and Science, 2016)
This work presents an experimental study of the unbalance compensation caused by the high speed railway substations in the high-voltage power grid with a shunt voltage source inverter based STATCOM. This experimental study is realized on a reduced scale prototype. The Control of inverter is implemented in a DSP card. The practical results presented in this paper are shown the performance of unbalance compensation by VSI_STATCOM in static and dynamic regime.